The Role of Religiousity in Mitigating the Effects of Technostress on Engaging Academic Fraud during Accounting Online Learning - Priyastiwi, Priyastiwi; Sriwidharmanely, Sriwidharmanely; Halim, Abdul (Jurnal Akuntansi, 2023)
The aim of this study is to examine how religion may help students overcome the effects of technostress, which heightens students' propensity for academic dishonesty during online learning. First, this study uses the self-determination theory (SDT) to describe the function of religion. We confirm that student’s technostress increases academic fraud during online learning using structural equation modelling (SEM). The study concludes that during hybrid learning, students with strong religiosity are more intrinsically motivated to prevent academic fraud than are students with low motivation. Students must be extremely motivated, confident in their cognitive flow, and convinced that using ICT won't cause them to engage in dysfunctional behavior in order to successfully adopt a virtual face-to-face application or learning management system in education. The study's last finding is that students' cognition can boost their positive emotion.